2010
DOI: 10.1007/s00442-010-1617-1
|View full text |Cite
|
Sign up to set email alerts
|

Short-term soil inorganic N pulse after experimental fire alters invasive and native annual plant production in a Mojave Desert shrubland

Abstract: Post-fire changes in desert vegetation patterns are known, but the mechanisms are poorly understood. Theory suggests that pulse dynamics of resource availability confer advantages to invasive annual species, and that pulse timing can influence survival and competition among species. Precipitation patterns in the American Southwest are predicted to shift toward a drier climate, potentially altering post-fire resource availability and consequent vegetation dynamics. We quantified post-fire inorganic N dynamics a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(46 citation statements)
references
References 48 publications
4
40
2
Order By: Relevance
“…Higher K availability after fire is more likely due to a high concentration of K in ash from the burned vegetation and litter (Debano and Conrad, 1978;Carreira and Niell, 1995). The post-fire increase in N and K also varied in its spatial distribution, as hypothesized and similar to other studies (Esque et al, 2010), with larger increases under Larrea canopies (UC microhabitat) than in the open inter-shrub areas. Although availability of Mg and Ca was greater under the Larrea canopy than in the open inter-shrub areas (overall), fire significantly increased these nutrients only in the OF microhabitat.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Higher K availability after fire is more likely due to a high concentration of K in ash from the burned vegetation and litter (Debano and Conrad, 1978;Carreira and Niell, 1995). The post-fire increase in N and K also varied in its spatial distribution, as hypothesized and similar to other studies (Esque et al, 2010), with larger increases under Larrea canopies (UC microhabitat) than in the open inter-shrub areas. Although availability of Mg and Ca was greater under the Larrea canopy than in the open inter-shrub areas (overall), fire significantly increased these nutrients only in the OF microhabitat.…”
Section: Discussionsupporting
confidence: 59%
“…Several studies have shown that nutrient concentrations (mainly N and K) are higher under Larrea canopies than in open inter-shrub areas (Samson, 1986;Titus et al, 2002;Mudrak et al, 2014). Fertility islands are crucial in desert systems because they help to maintain a diverse and productive annual plant community under the shrub canopies (Esque et al, 2010;Schafer et al, 2012). Many native annual species do not readily grow in the open inter-shrub areas, unlike the exotic species described above.…”
Section: Introductionmentioning
confidence: 92%
“…Nitrification increases after a fire if there is an accumulation of NH 4 + mineralized by the fire that is then converted to NO 3 2 (Bauhus et al 1993;Andersson et al 2004;Esque et al 2010). Effects of fire on mineralization and nitrification were short-lived in a burned Australian hummock grassland; in fact, the major differences in N turnover rates were between soils under and between hummocks, rather than between burned and unburned soils, indicating the importance of organic matter in driving mineralization and nitrification (Ford et al 2007).…”
Section: Effects Of Fire On Soil Microbiological Propertiesmentioning
confidence: 93%
“…Even if 100% of aboveground plant plus litter N is volatilized during a very hot fire, ecosystem N loss may only be 5-15%. Mineralization of N immobilized in plant tissue, litter, and SOM may temporarily increase productivity above prefire rates (Esque et al 2010), offsetting potential negative effects of N losses. This requires that vegetation be adapted to fire and resprout or reseed rapidly to take up the mineralized N. However, vegetation recovery may be slow in deserts because of low and variable precipitation (Abella 2009), potentially allowing nutrient loss.…”
Section: Changes In Soil Carbon (C) and Nitrogen (N) After Firementioning
confidence: 98%
“…In arid lands of the southwestern USA, for example, large disturbances caused by wildfires facilitate invasions by non-native grasses (Brooks and Matchett 2006). Total production of non-native annual grasses increases in response to elevated soil N in a post-fire environment (Esque et al 2010). Non-native species invasions are also facilitated by fine-scale disturbances that alter the physical characteristics of soil surfaces and create microhabitats conducive to seed entrapment that can lead to seedling survival and plant establishment (Chambers 2000).…”
Section: Introductionmentioning
confidence: 99%